Biodistribution of newly synthesized PHEA-based polymer-coated SPION in Sprague Dawley rats as magnetic resonance contrast agent - Park, Junsung (Dove Medical Press, 2013)
OBJECTIVES: The purpose of this study was to observe the pharmacokinetic behavior of newly synthesized biocompatible polymers based on polyhydroxyethylaspartamide (PHEA) to be used to coat an iron oxide core to make superparamagnetic iron oxide nanoparticles (SPION). MATERIALS AND METHODS: The isotopes [(14)C] and [(59)Fe] were used to label the polymer backbone (CLS) and iron oxide core (FLS), respectively. In addition, unradiolabeled cold superparamagnetic iron oxide nanoparticles (SPION/ULS) were synthesized to characterize particle size by dynamic light scattering, morphology by transmission electron microscopy, and in vivo magnetic resonance imaging (MRI). CLS and FLS were used separately to investigate the behavior of both the synthesized polymer and [Fe] in Sprague Dawley (SD) rats, respectively. Because radioactivity of the isotopes was different by β for CLS and γ for FLS, synthesis of the samples had to be separately prepared. RESULTS: The mean particle size of the ULS was 66.1 nm, and the biodistribution of CLS concentrations in various organs, in rank order of magnitude, was liver > kidney > small intestine > other. The biodistribution of FLS concentrations was liver > spleen > lung > other. These rank orders show that synthesized SPION mainly accumulates in the liver. The differences in the distribution were caused by the SPION metabolism. Radiolabeled polymer was metabolized by the kidney and excreted mainly in the urine; [(59)Fe] was recycled for erythrocyte production in the spleen and excreted mainly in the feces. The MR image of the liver after intravenous injection demonstrated that [Fe] effectively accumulated in the liver and exhibited high-contrast enhancement on T2-weighted images. CONCLUSION: This newly synthesized, polymer-coated SPION appears to be a promising candidate for use as a liver-targeted, biocompatible iron oxide MR imaging agent.